PENGAMBILAN KEPUTUSAN DALAM KEPEMIMPINAN PENDIDIKAN BERBASIS AGAMA, FILSAFAT, PSIKOLOGI, DAN SOSIOLOGI - Hadi Laksono; Majeri Majeri; Ujang Nurjaman; Muhammad Al Mighwar (Fakultas Agama Islam Universitas Wiralodra, 2022)
This study aims to describe and analyze the what, why, and how of decision making in educational leadership based on religion, philosophy, psychology, and sociology. From this study it was concluded that decision making in educational leadership is the optimal effort of educational leaders to make permanent and appropriate decisions which are: (1) based on religion means based on God's teachings that require justice, by not favoritism, without hatred, not following the winds. lust, do not twist the facts, and dare to testify; (2) based on philosophy means based on knowledge and inquiry with reason that respects the existence of free and responsible human beings, by democratic way (non-directive, accommodative, and participatory); (3) based on psychology means based on psychology that emphasizes the basic drives (hormic) of human behavior, through instinctive approaches (perceptual, emotional, and motoric) and personality (disposition, temperament, and character methods); and (4) based on sociology means based on social science that pays attention to networks of social actors, by way of visual identification of networks and centralization of intermediaries